2021
DOI: 10.1038/s41467-021-24602-x
|View full text |Cite|
|
Sign up to set email alerts
|

Turn-key mapping of cell receptor force orientation and magnitude using a commercial structured illumination microscope

Abstract: Many cellular processes, including cell division, development, and cell migration require spatially and temporally coordinated forces transduced by cell-surface receptors. Nucleic acid-based molecular tension probes allow one to visualize the piconewton (pN) forces applied by these receptors. Building on this technology, we recently developed molecular force microscopy (MFM) which uses fluorescence polarization to map receptor force orientation with diffraction-limited resolution (~250 nm). Here, we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Platelets are a useful model because of their small size and their ability to generate force. 34, 36, 37, 38, 39, 40 Understanding platelet force is also biomedically relevant in the study of clotting disorders, wound healing, and drug interactions for common cardiovascular diseases. 41, 42 Platelets were cultured on RS and RU probe for 1 hour before activation with 10 µM ADP for 10 minutes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Platelets are a useful model because of their small size and their ability to generate force. 34, 36, 37, 38, 39, 40 Understanding platelet force is also biomedically relevant in the study of clotting disorders, wound healing, and drug interactions for common cardiovascular diseases. 41, 42 Platelets were cultured on RS and RU probe for 1 hour before activation with 10 µM ADP for 10 minutes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This design strategy provides a way to monitor the real-time molecular tension during cell spreading. The combination of RGD-ligand-DNA tension sensors with super-resolution imaging technology takes the study of cell mechanics to another ultrastructure level [ [52] , [53] , [54] , [55] ]. In our study, we observed that the requirement of molecular tension on integrins is positively correlated with FA size.…”
Section: Discussionmentioning
confidence: 99%
“…DNA‐based hairpin probe offers the flexibility to fine‐tune the force regime for measuring integrin dynamics, making it ideally suited for live‐cell tension imaging [19, 20] . Tension imaging using structured illumination microscopy (SIM) enabled super‐resolution force mapping with orientation but the resolution was lower than DNA‐PAINT [21, 22] . An improved DNA‐PAINT‐based super‐resolution method for fast, live‐cell tension imaging is crucial for understanding integrin‐mediated cellular mechanics.…”
Section: Figurementioning
confidence: 99%
“…[19,20] Tension imaging using structured illumination microscopy (SIM) enabled super-resolution force mapping with orientation but the resolution was lower than DNA-PAINT. [21,22] An improved DNA-PAINT-based super-resolution method for fast, live-cell tension imaging is crucial for understanding integrin-mediated cellular mechanics. Here we developed a new strategy using a molecular beacon (MB) as the imager molecule that only becomes fluorescent upon binding to target sequences (Figure 1), eliminating the drawbacks of traditional DNA-PAINT while retaining all its advantages.…”
Section: Dna-pointmentioning
confidence: 99%